MENGUAK AGENDA KOLONIAL DALAM PERINTAH PEMBANTAIAN ULANGAN 7:1-11 - Owen Brian Kawengian (Institut Agama Kristen Negeri Manado, 2025)
It is undeniable that the Old Testament in the Christian Bible contains the extremely violent narratives such as slaughter and genocide. One of them is Deuteronomy 7:1-11, which has been the subject of discussion and debate for a long time among scholars because of the nature of the narrative, which contradicts the image of a merciful God in Christian faith. More terribly, the text, and other similar texts, had been used to legitimize colonization and genocide of native people by European colonizers in the 18th-19th centuries. As a text that has been studied and discussed frequently, research on the extermination command in Deuteronomy 7 has often been carried out. However, what differentiates this article from another is the use of a postcolonial criticism that scrutinizes the agenda of colonialism not only in the narrative within the text but also in the text's production process. As a result, this article offers two important key points as an alternative way to interpret the narrative of the massacre command in the text.